2020
DOI: 10.55563/clinexprheumatol/ck090i
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile idiopathic arthritis patients have a distinct cartilage and bone biomarker profile that differs from healthy and knee-injured children

Abstract: ObjectiveJoint destruction is a hallmark of juvenile idiopathic arthritis (JIA). Clinical evaluation and radiographic imaging are current methods to identify destruction. Biomarkers could aid an earlier and more sensitive diagnosis. Our aim was to investigate levels of bone and cartilage degradation biomarkers in JIA patients, compared to healthy children or juveniles with knee injuries. Methods Triple-paired synovial fluid, plasma and urine samples from 29 JIA patients were compared to 61 plasma samples from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
1
1
Order By: Relevance
“…Thus, our results and those of Bjørnhart et al [ 43 ] and Urakami et al [ 44 ] confirm the above thesis. In contrast to our results, Struglics et al [ 40 ] showed that JIA patients are characterized by an increase in blood COMP levels. These discrepancies are likely the result of the cited authors’ qualification of patients into three types of arthropathy, different disease duration, and inconsistent pharmacotherapy, which might determine the turnover of the ECM, since we have shown that COMP metabolism in patients with JIA, both before and during ETA therapy, remains related to the activity of proteolytic processes, stimulated by ADAMTS4 and ADAMTS5 concentrations, as well as anabolic processes, related to PDGF-BB concentrations.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, our results and those of Bjørnhart et al [ 43 ] and Urakami et al [ 44 ] confirm the above thesis. In contrast to our results, Struglics et al [ 40 ] showed that JIA patients are characterized by an increase in blood COMP levels. These discrepancies are likely the result of the cited authors’ qualification of patients into three types of arthropathy, different disease duration, and inconsistent pharmacotherapy, which might determine the turnover of the ECM, since we have shown that COMP metabolism in patients with JIA, both before and during ETA therapy, remains related to the activity of proteolytic processes, stimulated by ADAMTS4 and ADAMTS5 concentrations, as well as anabolic processes, related to PDGF-BB concentrations.…”
Section: Discussioncontrasting
confidence: 99%
“…This confirms the significant structural abnormalities of the cartilage matrix in children with JIA. This is due to the fact that predominant tissue localization of COMP is articular cartilage, while small amounts of the protein in question are also found in tendons, meniscus, or synovial membrane [ 40 ]. Deficiency of this protein may, on the one hand, promote the degradation of collagenous cartilage tissue, but on the other hand, COMP deficiency may result from pathological joint remodeling of the ECM.…”
Section: Discussionmentioning
confidence: 99%